Designing a Model for Evaluating Ethical Behavior in Iranian Organizations in the Light of the Quran and Nahj al-Balagha - Ali Asqhar Pour-Ezzat; Golara Pourmojarab; Hasan Zarei Matin; Hamid Reza Yazdani (اخلاق وحیانی)
Ethics is one of the most widely used words in social life that has been expressed in Iranian organizations' goals and policies in recent decades. However, there is no precise definition of ethics in the organization or a standard that can distinguish ethics from non-ethics in any circumstances. Ethics and its related theories are strongly dependent on the cultural and religious context of the society; therefore, the definition of ethical standards must be done according to the valuable beliefs of the intended community; therefore, the need to determine native ethical criteria appropriate to the beliefs and values of the community for Iranian organizations is felt. For this purpose, by analyzing the content, the Holy Qur'anic verses and Nahj al-Balagha's propositions were studied and finally, 97 basic themes, 13 organizing themes, and two overarching themes, action's goodness and subject's goodness, have been counted. The criteria for action's goodness deal with the organizer themes of considering responsibility as a trust, respect for justice, benevolence, moderation, the preservation of human dignity, the nature of action, the worldly and afterlife's consequences of acts. And the criteria for subject's goodness are organizer themes of the faith to God, piety, good intention and the appropriateness for acting.